2013
DOI: 10.3748/wjg.v19.i9.1349
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the vaccination in inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) is associated with conditions that may predispose to infections, such as the lack of an appropriate innate immune response to infectious agents, malnutrition, surgery, and immunosuppressive and biological drugs. Some of these infections may be preventable by vaccination. Therefore, for this particular patient population, the benefits of implementing a well-established immunization protocol in daily clinical practice are potentially even greater than for the general population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…There is conflicting evidence in the IBD literature regarding immunogenicity of tetanus vaccination . One study in patients with rheumatoid arthritis on methotrexate alone or methotrexate plus rituximab identified suboptimal, albeit similar, response to tetanus toxoid (42.3% vs 39.1% response, respectively) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is conflicting evidence in the IBD literature regarding immunogenicity of tetanus vaccination . One study in patients with rheumatoid arthritis on methotrexate alone or methotrexate plus rituximab identified suboptimal, albeit similar, response to tetanus toxoid (42.3% vs 39.1% response, respectively) .…”
Section: Resultsmentioning
confidence: 99%
“…47 There is conflicting evidence in the IBD literature regarding immunogenicity of tetanus vaccination. 49 One study in patients with rheumatoid arthritis on methotrexate alone or methotrexate plus rituximab identified suboptimal, albeit similar, response to tetanus toxoid (42.3% vs 39.1% response, respectively). 50 Patients with bullous pemphigoid had similar immune responses to tetanus toxoid compared with healthy age-matched controls, but immunosuppression regimen at the time of vaccination is unknown.…”
Section: Tetanus Diphtheria and Pertussis Vaccinementioning
confidence: 99%
“…However, one study has shown low response rate to hepatitis B vaccine in immunosuppressed patients with inflammatory bowel disease[14]. Other investigations have revealed that immunosuppressive regimens used by mothers do not affect the offsprings’ immune status[15].…”
Section: Discussionmentioning
confidence: 99%
“…If infection is present by testing before vaccination, other specific tests should be performed, and the patient should be evaluated by a specialist for the need of treatment. The importance of care in relation to HVB infection consists in the fact that reactivation of HBV is a well-described complication of immunosuppression [4,5,7].…”
Section: • Blood Transfusionmentioning
confidence: 99%
“…In addition to the hepatitis B vaccine, the patient should also receive the following vaccines before starting the treatment with biological therapy [4][5][6][7]9]: It is important to emphasize that immunosuppressed patients do not respond properly to immunization. In addition, patients receiving biological therapy cannot be vaccinated with live attenuated virus (varicella zoster, yellow fever, measles, mumps, and rubella) [9].…”
Section: Vaccinationmentioning
confidence: 99%